Lens-Free On-Chip Quantitative Phase Microscopy for Large Phase Objects Based on a Biplane Phase Retrieval Method - Yufan Chen; Xuejuan Wu; Yang Chen; Wenhui Lin; Haojie Gu; Yuzhen Zhang; Chao Zuo (Sensors)
Lens-free on-chip microscopy (LFOCM) is a powerful computational imaging technology that combines high-throughput capabilities with cost efficiency. However, in LFOCM, the phase recovered by iterative phase retrieval techniques is generally wrapped into the range of −<semantics>π</semantics> to <semantics>π</semantics>, necessitating phase unwrapping to recover absolute phase distributions. Moreover, this unwrapping process is prone to errors, particularly in areas with large phase gradients or low spatial sampling, due to the absence of reliable initial guesses. To address these challenges, we propose a novel biplane phase retrieval (BPR) method that integrates phase unwrapping results obtained at different propagation distances to achieve accurate absolute phase reconstruction. The effectiveness of BPR is validated through live-cell imaging of HeLa cells, demonstrating improved quantitative phase imaging (QPI) accuracy when compared to conventional off-axis digital holographic microscopy. Furthermore, time-lapse imaging of COS-7 cells in vitro highlights the method’s robustness and capability for long-term quantitative analysis of large cell populations.